Diversidad de vertebrados acuáticos de tres humedales urbanos de la ciudad de Buenos Aires - Llamazares Vegh, S. (2012)
The urban wetlands are sites of high biodiversity that are under a great anthropogenic pressure. In the city of Buenos Aires, one of the more important areas of recreation is constituted by Parque Tres de Febrero (well-known as like “Bosques de Palermo”), that conforms a green zone of 25 ha. In this area there are artificial wetlands of diverse physical characteristics. In the present work, the goal is to determine vertebrate’s diversity in these urban aquatic enviroments in order to evaluate the degree of impact of the recreational activity on the conservation of the vertebrates associated to the water bodies. The study was carried out in three artificial lagoons included in the park: Regatas, Rosedal and Planetario. Altogether, seventeen species of fish (Prochilodus lineatus, Oligosarcus jenynsii, Cheirodon interruptus, Bryconamericus iheringii, Hoplias malabaricus, Hypostomus commersoni, Rhamdia quelen, Pimelodus albicans, Pimelodus maculatus, Cyprinus carpio carpio, Cnesterodon decemmaculatus, Gambusia affinis, Jenynsia multidentata, Synbranchus marmoratus, Australoheros facetus, Gymnogeophagus meridionalis and Crenicichla scottii), eighteen species of birds (Podiceps rolland, Podilymbus podiceps, Podiceps major, Phalacrocorax olivaceus, Ardea alba, Egretta thula, Butorides striatus, Nycticorax nycticorax, Anas georgica, Anas platyrhynchos, Anas platyrhynchos domesticus, Anser anser, Cairina moschata, Netta peposaca, Aramus guarauna, Fulica armillata, Fulica leucoptera and Chloroceyle amazona), three species of turtles (Phrynops hilarii, Trachemys scripta elegans and Trachemys venusta) and one species of mammal were registered (Myocastor coipo). Among these species, eight are introduced: two fishes (Cyprinus carpio carpio and Gambusia affinis), two turtles (Trachemys scripta elegans and Trachemys venusta) and four birds (Anas platyrhynchos, Anas platyrhynchos domesticus, Anser anser and Cairina moschata). Regatas was the site with greater diversity of fishes (n=17) that represents a 10.43% of Río de la Plata’s ichthyofauna (n=163). This site lodges a 13% of the bird species associated to registered water bodies in the City of Buenos Aires (n=107). When comparing the specific richness among lagoons, we found high similarity between Regatas and Planetarium. Also, both sites presented the greatest specific richness of fish during the months of January and February. From this preliminary study it was possible to describe and to differentiate each lagoon by its fauna and physical characteristics, and also it constitutes the base to continue with further studies of communities which allow the development of the necessary guidelines of handling for the protection of Lagos Tres de Febrero.